2017
DOI: 10.1002/slct.201700693
|View full text |Cite
|
Sign up to set email alerts
|

Cu(II) and Ni(II) Complexes of Anthracene‐Affixed Schiff Base: A Conflict between Covalent and Stacking Interactions with DNA Bases

Abstract: Four new mononuclear complexes [Cu(L1)Cl 2 ] (1), [Ni(L1)Cl 2 ] (2), [Cu(L2)Cl 2 ] (3) and [Ni(L2)Cl 2 ] (4), where L1 (1-(anthracen-9-yl)-N-(1H-benzo[d]imidazole-2-yl)methanimine) and L2 (1-(anthracen-9-yl)-N-(benzo[d]thiazol-2yl)methanimine) have been synthesized and characterized by various spectral and electro analytical techniques. The molecular structure of the ligands L1 and L2 were determined by the single crystal XRD method. The absorption and emission spectral approaches revealed that these complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Therefore, the small difference in their binding affinity is most possibly because of the two reasons: (a) there are different metal ions present in the respective complexes (Cu(II) in 1 ; Mn(II) in 2 ; Zn(II) in 3 ); (b) the degree of distortion of the square pyramidal coordination geometry around the metal centers in 1 – 3 is also different. Comparing their K b values with the values reported for anthracence‐based ligand containing similar mononuclear metal complexes, it can also be said that the analogous binding affinities are observed for the present complexes [83–85] . In all, the observed results are in agreement with the results from the spectral analyses mentioned above.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the small difference in their binding affinity is most possibly because of the two reasons: (a) there are different metal ions present in the respective complexes (Cu(II) in 1 ; Mn(II) in 2 ; Zn(II) in 3 ); (b) the degree of distortion of the square pyramidal coordination geometry around the metal centers in 1 – 3 is also different. Comparing their K b values with the values reported for anthracence‐based ligand containing similar mononuclear metal complexes, it can also be said that the analogous binding affinities are observed for the present complexes [83–85] . In all, the observed results are in agreement with the results from the spectral analyses mentioned above.…”
Section: Resultssupporting
confidence: 88%
“…Comparing their K b values with the values reported for anthracence-based ligand containing similar mononuclear metal complexes, it can also be said that the analogous binding affinities are observed for the present complexes. [83][84][85] In all, the observed results are in agreement…”
Section: Comparison Of Dna Binding Affinities Of the Complexessupporting
confidence: 83%
“…However, the fluorescence intensity of DNA–EB system was quenched to a much larger extent in the case of complex 1 indicated that the EB molecule was almost completely deranged from the original binding site of DNA leading to the intercalation of aromatic ligand scaffold. But in the case of complex 2 the intensity of fluorescence of DNA–EB was slightly decreased which suggests partial intercalation along with constriction of DNA helix via electrostatic binding mode . The quenching constant K sv has been computed from the Stern–Volmer equation : true4ptnormalIo/normalI=14pt+4ptnormalKsv[Q] …”
Section: Dna Binding Studiesmentioning
confidence: 99%
“…In the absence of CT‐DNA, Pc4 and Pc5 had a couple of waves with the cathodic (EPc) and anodic peak potential (EPa) being −0.55 V (EPc) and −0.71, and 0.61 V (EPa) for Pc4 in Figure (red line), and −0.34 V, 0.69 V (EPc) and −0.5, 0.1 and 0.9 V (Epa) for Pc5 in Figure (red Line)), respectively. In the presence of CT‐DNA, after the addition of CT‐DNA to Pc4 andd Pc5 , the cyclic voltammetric peak currents apparently decreased, which is an indicator of the interaction between the compounds and CT‐DNA . Decrease in the voltammetric currents in the presence of CT‐DNA may be a sign of low diffusion of Pc4 and Pc5 that were binding to CT‐DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, when a compound binds to DNA, the DNA helix extends as DNA base pairs are separated to coordinate the binding ligand, which results in increased DNA viscosity. In contrast to the compound which binds to DNA via partial non‐intercalation, this could diminish the length of DNA by distorting its viscosity . DNA binding mode of Pc4 and Pc5 was also investigated by viscosity measurements.…”
Section: Resultsmentioning
confidence: 99%